2019
DOI: 10.3390/app9183684
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Surface Roughness of 304 Stainless Steel and Multi-Objective Optimization of Cutting Parameters Based on GA-GBRT

Abstract: Establishing and controlling the prediction model of a machined surface quality is known as the basis for sustainable manufacturing. An ensemble learning algorithm—the gradient boosting regression tree—is incorporated into the surface roughness modeling. In order to address the problem of a high time cost and tendency to fall into a local optimum solution when the grid search and conjugate gradient method is adopted to obtain the super-parameters of the ensemble learning algorithm, a genetic algorithm is emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…For example, Kumar [4] adopted surface roughness and material removal rate (MRR) as objectives to optimize the cutting parameters in turning C360 copper alloy. Zhou et al [5] obtained the Pareto optimal solution with the maximum MRR and the minimum surface roughness in turning AISI 304 based on the genetic algorithm gradient boosting regression tree (GA-GBRT) model they established. Their experimental results demonstrated that MRR can be improved by increasing cutting depth and cutting speed in a small range of surface roughness variations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kumar [4] adopted surface roughness and material removal rate (MRR) as objectives to optimize the cutting parameters in turning C360 copper alloy. Zhou et al [5] obtained the Pareto optimal solution with the maximum MRR and the minimum surface roughness in turning AISI 304 based on the genetic algorithm gradient boosting regression tree (GA-GBRT) model they established. Their experimental results demonstrated that MRR can be improved by increasing cutting depth and cutting speed in a small range of surface roughness variations.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, according to the results of the study, they determined that the input that affects the SR the most are the feed rate and then the axial vibration. Zhou et al [ 154 ] created an algorithm based on the genetic-gradient boosting regression tree for the optimization of cutting parameters and SR estimation by turning AISI 304 stainless steel. They compared this model created with an optimized artificial neural network and support vector regression method.…”
Section: Indirect Tool Condition Monitoring Systemsmentioning
confidence: 99%
“…Zhou et al [15] investigate the turning process, where the cutting speed, the feed and the depth of cut were varied. The surface roughness prediction model was built to the measured data and use genetic-gradient boosting regression tree method.…”
Section: Artificial Intelligence Approachmentioning
confidence: 99%